Role of Social Media for Movie Marketing in the Nepalese Film Industry - Pradhan, Bijay Lal; Satyal, Dipen; KC, Abin; Joshi, Nabin Raj; Pradhan, Ambira (Journey for Sustainable Development and Peace Journal, 2026)
This study analyzes how ticket purchasing behaviour in the Nepalese film industry is influenced by Social Media Marketing Campaigns (SMMC) and Preview Analysis (PA). A survey of 173 active social media users using a descriptive, cross-sectional design shows that platforms such as Facebook, YouTube, Instagram, and TikTok play a central role in how audiences discover and decide on films. The study observed that trailers, reviews, influencer content, and electronic word-of-mouth were statistically significant predictors of movie-going intentions. Social media is now the main source of film information, with audiences relying on SMMC and PA before deciding to watch, revealing that Nepal’s movie business is undergoing a digital transformation similar to other developing economies. The results highlight the need for organized, data-driven marketing strategies: better online campaigns and well-timed previews can boost visibility, deepen audience relationships, and raise box-office returns. These findings have major implications for filmmakers, marketers, and industry planners aiming to optimize digital promotion in a rapidly changing media landscape.